2006
DOI: 10.1007/s00421-006-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Muscle triacylglycerol and hormone-sensitive lipase activity in untrained and trained human muscles

Abstract: During exercise, triacylglycerol (TG) is recruited in skeletal muscles. We hypothesized that both muscle hormone-sensitive lipase (HSL) activity and TG recruitment would be higher in trained than in untrained subjects in response to prolonged exercise. Healthy male subjects (26 +/- 1 years, body moss index 23.3 +/- 0.5 kg m(-2)), either untrained (N = 8, VO(2max) 3.8 +/- 0.2 l min(-1)) or trained (N = 8, VO(2max) 5.1 +/- 0.1 l min(-1)), were studied. Before and after 3-h exercise (58 +/- 1% VO(2max)), a biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…HSL protein expression was not changed by exercise training in the present study, which was supported by findings in a study in rodents in which HSL protein expression was not different in skeletal muscle of swim-trained rats compared with sedentary controls (10). Furthermore, muscle HSL activity was similar at basal (rest) in untrained and trained male subjects and no differences were seen in IMTG between the two groups (18).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HSL protein expression was not changed by exercise training in the present study, which was supported by findings in a study in rodents in which HSL protein expression was not different in skeletal muscle of swim-trained rats compared with sedentary controls (10). Furthermore, muscle HSL activity was similar at basal (rest) in untrained and trained male subjects and no differences were seen in IMTG between the two groups (18).…”
Section: Discussionsupporting
confidence: 91%
“…It is not known whether ATGL protein expression in skeletal muscle might be affected by physical activity, but a hypothesis could be that changes in muscle activity would induce changes in ATGL protein expression like many other proteins (19). An increased ATGL expression with endurance training might be expected since some (18,20,36) but not all (1, 26) endurance training studies have indicated that utilization of IMTG during exercise is enhanced in the endurancetrained state. This increased lipolytic capacity does not seem to relate to changes in HSL protein expression, since HSL protein levels are not changed by endurance training in rat skeletal muscle (10) and in human subjects HSL content is similar in untrained and trained skeletal muscle (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serial transverse muscle sections were cut from the embedded muscle tissue and then stained for myofibrillar ATPase to identify fibre type composition [18]. Muscle triacylglycerol content was analysed as previously described [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Muscle glycogen content was analysed by the hexokinase method [24]. Muscle triacylglycerol (TG) content was analysed as described elsewhere [25]. Fibre type, size and capillary density were analysed as described elsewhere [26][27][28].…”
Section: Analytical Proceduresmentioning
confidence: 99%